2017
DOI: 10.1155/2017/7924148
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dose of Epidural Dexmedetomidine Added to Ropivacaine for Epidural Labor Analgesia: A Pilot Study

Abstract: Background Dexmedetomidine combined with local anesthetics can decrease the concentration of epidural ropivacaine. However, the optimal dose of epidural dexmedetomidine combined with ropivacaine for labor analgesia is still uncertain. This study investigated the effect of adding different dose of epidural dexmedetomidine to ropivacaine during epidural labor analgesia. Methods One hundred women were randomly assigned to one of the four groups (Groups A, B, C, and D received 0.25, 0.5, 0.75, and 1 μg/ml of dexme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 15 publications
2
19
0
1
Order By: Relevance
“…The dose used in the present study was determined according to a preliminary study, which indicated that for epidural labor analgesia the optimal concentration of Dex was 0.5 µg/ml when combined with 0.1% ropivacaine; therefore, 0.5 µg/ml Dex was used as an adjuvant to epidural ropivacaine in labor analgesia. Furthermore, the addition of 5 µg intrathecal Dex to 10 µg fentanyl lengthened the analgesia duration and lowered the incidence of adverse effects compared with the use of intrathecal 10 µg Dex or intrathecal 20 µg fentanyl alone (28). Therefore, 0.25 µg/ml Dex and 0.25 µg/ml sufentanil were used as adjuvants in combination with 0.1% ropivacaine epidurally for labor analgesia in the present study.…”
Section: Discussionmentioning
confidence: 78%
“…The dose used in the present study was determined according to a preliminary study, which indicated that for epidural labor analgesia the optimal concentration of Dex was 0.5 µg/ml when combined with 0.1% ropivacaine; therefore, 0.5 µg/ml Dex was used as an adjuvant to epidural ropivacaine in labor analgesia. Furthermore, the addition of 5 µg intrathecal Dex to 10 µg fentanyl lengthened the analgesia duration and lowered the incidence of adverse effects compared with the use of intrathecal 10 µg Dex or intrathecal 20 µg fentanyl alone (28). Therefore, 0.25 µg/ml Dex and 0.25 µg/ml sufentanil were used as adjuvants in combination with 0.1% ropivacaine epidurally for labor analgesia in the present study.…”
Section: Discussionmentioning
confidence: 78%
“…Epidural morphine has previously been indicated to not be associated with neonatal outcome (35). Previous studies have also suggested that epidural dexmedetomidine has no adverse effects on neonates (1,2,(9)(10)(11)(12). Similar results were obtained in the present study with co-administration of epidural dexmedetomidine and morphine.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic meta-analysis demonstrated that dexmedetomidine as an adjuvant in epidural anesthesia provided improved sedation and analgesia with a well-documented safety profile (7). Several studies involving epidural dexmedetomidine in obstetric populations have been published: Dexmedetomidine added to combined spinal (bupivacaine)-epidural (fentanyl) anesthesia for cesarean section (1,2); combined epidural dexmedetomidine and ropivacaine for post-cesarean analgesia (8); and epidural dexmedetomidine combined with ropivacaine or bupivacaine for labor analgesia (9)(10)(11)(12). All these previous studies demonstrated the potentiating effect of epidural dexmedetomidine on neuraxial analgesia, with minimal side effects (1,2,(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that anesthetics may inhibit the maternal temperature regulation center. Dexmedetomidine, an a 2 -adrenergic agonist, has been used successfully for epidural labor analgesia, with fewer side effects [6][7][8]. We hypothesized that dexmedetomidine could reduce the incidence of intrapartum fever during labor analgesia without increasing adverse events.…”
Section: Introductionmentioning
confidence: 99%